2013
DOI: 10.1242/jcs.125476
|View full text |Cite
|
Sign up to set email alerts
|

Connexin30 mediated intercellular communication plays an essential role in epithelial repair in the cochlea

Abstract: SummaryA role for connexin (Cx)30 in epithelial repair following injury was examined in the organ of Corti, the sensory epithelium of the cochlea. In this tissue, lesions caused by loss of the sensory hair cells are closed by the supporting cells that surround each one. Gap junctions in which Cx30 is the predominant connexin are large and numerous between supporting cells. In mice carrying a deletion in the gene (Gjb6) that encodes Cx30, the size and number of gap junction plaques, and the extent of dye transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 33 publications
1
35
0
1
Order By: Relevance
“…Swelling has been previously reported following ototoxic and noise traumas (Fredelius 1988;Flock et al 1999;Ahmad et al 2003;Abrashkin et al 2006;Taylor et al 2012;Forge et al 2013). A possible trigger for this event is altered ion transport coupled with intercellular signaling between dying hair cells and supporting cells (Piazza et al 2007;Forge et al 2013). Thus, phalangeal swelling of DCs can serve as a protective ion buffering mechanism in the lesioned organ of Corti.…”
Section: Discussionmentioning
confidence: 89%
“…Swelling has been previously reported following ototoxic and noise traumas (Fredelius 1988;Flock et al 1999;Ahmad et al 2003;Abrashkin et al 2006;Taylor et al 2012;Forge et al 2013). A possible trigger for this event is altered ion transport coupled with intercellular signaling between dying hair cells and supporting cells (Piazza et al 2007;Forge et al 2013). Thus, phalangeal swelling of DCs can serve as a protective ion buffering mechanism in the lesioned organ of Corti.…”
Section: Discussionmentioning
confidence: 89%
“…For example, in wounded skin, up-regulation of Cx30 and Cx26 in all epidermal keratinocyte layers, and a concomitant decrease in Cx43 at the wound edge, are proposed to co-ordinate the keratinocyte wound healing response (Coutinho et al, 2003;Churko and Laird, 2013). In the damaged cochlea, Cx30 is also important for coordinating a wound healing response after sensory hair cell death (Forge et al, 2013). In this instance, supporting cells expand to fill the voids left by dead hair cells and restore epithelial tight junction integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In this instance, supporting cells expand to fill the voids left by dead hair cells and restore epithelial tight junction integrity. In Cx30 −/− mice, supporting cells not only display defects in repairing the space left by dead hair cells, they also develop a highly unusual migratory phenotype, despite still expressing Cx26, suggesting that Cx30 plaques may be important in controlling cell responses to injury (Forge et al, 2013). The inability of terminally differentiated keratinocytes and cochlear supporting cells to proliferate suggests that long-lived Cx30 gap junctions may help to regulate GJIC or cell-cell adhesion properties to collectively coordinate and control wound healing responses.…”
Section: Discussionmentioning
confidence: 99%
“…A typical barrier complex includes tight junctions, adherens junctions, and desmosomes. Previous studies have suggested that different types of intercellular junctions are important to normal ear function (Forge et al, 2013, Hardison et al, 2005, Zhu et al, 2013. Desmosome function in the organ of Corti is a largely unexplored area.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to various types of system development (Cenci and Gould, 2005, Gao et al, 2013, Han et al, 2011, Janicke et al, 2010, Sanchez-Calderon et al, 2007. For example, the GRH family is important to epithelial barrier development and post-wounding barrier repair via regulation of junction protein expression and to epithelial adhesion, which is essential to organ development (Hama) (Forge et al, 2013, Zhu et al, 2013. Within this family, GRHL2 has been confirmed to be related to DFNA28.…”
Section: Introductionmentioning
confidence: 99%